The best optical zone for small-incision lenticule extraction in high myopic patients. Issue 9 (September 2020) - Zhang, Jia-Hao; Wang, Shu-Rong; He, Yu-Xi; Yao, Bo-Yuan; Zhang, Yan
Abstract : The purpose of this review is to find the optimal parameters of SMILE so that surgeons can provide reference recommendations for patients with high myopia to choose a reasonable procedure. Abstract : Small-incision lenticule extraction (SMILE) is an effective and safe procedure for the correction of myopia due to minimally invasive and noncorneal flap surgery. However, the SMILE procedure has certain requirements for corneal cap thickness, attempted refractive correction, residual stromal bed thickness, and optical zone diameter, which sometimes make surgeons hesitant to choose SMILE or other refractive surgeries. The requirements limit its use in patients with high myopia. The purpose of this review was to find the optimal parameters of SMILE through discussing the best optical zone for high myopic patients, the visual quality of different optical zones, the choice of corneal cap thickness, and their effects on corneal biomechanical parameters, so surgeons can provide reference recommendations for patients with high myopia in choosing a reasonable and safe procedure.